PERLINDUNGAN HUKUM BAGI PEMILIK MEREK TERKENAL BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Indira Hastuti (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
Brand protection is not only given to local brands but also to well-known brands that already exist but have not been registered in Indonesia. Protection of well-known brands is given both preventive and repressive protection. Based on this, it is interesting to raise the issue of legal protection for well-known owners based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Based on the discussion it can be concluded that Law Number 20 of 2016 concerning Trademarks and Geographical Indications provides legal protection to owners of well-known brands as stipulated in Article 21 paragraph (1), Article 76 paragraph (1) and Article 83.